Tuberous sclerosis with giant internal carotid artery aneurysm resulting left third nerve palsy: A case report (Bangladesh Medical Journal, 2014)
Tuberous sclerosis is an autosomal dominant hereditary condition with many varied forms of clinical presentation. The most frequent cutaneous findings in tuberous sclerosis include multiple angiofibromas, hypopigmented macules, periungual fibromas and shagreen patch. It is characterized by the development of hamartomatous growths in many organs. We present a case of tuberous sclerosis with a giant left internal carotid artery aneurysm causing pulsatile proptosis, left sided ptosis, anisocoria and papillary mydriasis indicative of left third cranial nerve palsy. DOI: http://dx.doi.org/10.3329/bmj.v43i2.21393 Bangladesh Med J. 2014 May; 43 (2): 103-105